Recently Strengthened Influence of ENSO on the Wintertime East Asian Surface Air Temperature - Hainan Gong; Lin Wang; Wen Chen (Atmosphere, 2019)
Previous studies have indicated that El Niño–Southern Oscillation (ENSO) exerts a significant influence on the East Asian winter climate. This study reveals an interdecadal strengthening of the connection between ENSO and the East Asian surface air temperature (EAT) connection around the late 1990s and investigates the reason for this change. Before the late 1990s, the influence of ENSO on the EAT was weak, and the ENSO-related southerly wind anomalies were confined to the south of 30° N of East Asia. After the late 1990s, by contrast, ENSO’s influence became stronger and capable of extending northward to 50° N of East Asia. The decadal strengthening of the link between ENSO and EAT is primarily modulated by the magnitudes of the ENSO-related Kuroshio anticyclone. The intensity of the Kuroshio anticyclone contributes more than 50% of the variance of the oscillational ENSO–EAT variability. Further investigation indicates that the recovered magnitude of the Kuroshio anticyclone after the late 1990s has been closely tied to the eastward shrinking of the Aleutian Low (AL) pattern, which has weakened the link of atmospheric circulation between the AL and Kuroshio Extension region. Therefore, the offset effect of the AL-induced negative (positive) sea level pressure (SLP) anomalies on the El Niño (La Niña)-induced positive (negative) SLP anomalies over the Kuroshio Extension has also been weakened, which has facilitated the recovery of the significant influence of ENSO on the EAT.